Atomic structure of ZrO2-doped Li2O–SiO2-based multi-component glasses revealed by molecular dynamics–reverse Monte Carlo modeling - Toyoda, R.; Usui, K.; Hirota, T.; Kimura, K.; Onodera, Y.; Cicconi, Maria Rita; Belli, Renan; Brehl, Martin; Lubauer, Julia; Lohbauer, Ulrich; Tajiri, H.; Ikeda, K.; et al. (Journal of Non-Crystalline Solids, 2023)
Structural model of ZrO2-doped Li2O–SiO2-based multi-component glass, which is developed as a mother material for high-strength glass-ceramics, is constructed by the molecular dynamics–reverse Monte Carlo (MD–RMC) method based on anomalous X-ray and neutron scattering data. In particular, we have succeeded in extracting reliable local structural information around Zr from the MD–RMC model. It was found that a significant fraction of edge-sharing structural units was formed around Zr–O and Li–O polyhedra, resulting in a densely packed configuration of O atoms. This configuration was manifested by a very sharp principal peak in the neutron scattering data. Our model suggested that both the Zr and Li ions are incorporated in the glass as distorted ZrO6 octahedra and distorted LiO4 tetrahedra, respectively. These structural features are discussed in terms of the crystallization behavior of this material.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Anomalous X-ray scatteirng; Glass-ceramics; Molecular dynamics simulation; Neutron scattering; Reverse Monte Carlo

Bioactive glass coating using aerosol deposition - Eckstein, Udo; Detsch, Rainer; Khansur, Neamul Hayet; Brehl, Martin; Deisinger, Ulrike; de Ligny, Dominique; Boccaccini, Aldo R.; Webber, Kyle Grant (Ceramics International, 2019)
This work demonstrates the successful deposition of bioactive glass (BG)45S5 coatings on various metallic and ceramic substrates at room temperature under low vacuum condition by using aerosol deposition (AD). This room temperature and particle impact consolidation-based deposition method enabled us to deposit well-adhered and dense BG coatings directly on metallic and ceramic substrates. In vitro tests with human osteoblast-like cells on substrates with a 45S5 BG coating demonstrated high cell activity on the surfaces. All tested materials exhibited high in vitro biocompatibility as no inhibition in cell proliferation could be observed. The utilization of AD process for achieving non-crystalline BG coatings is promising for practical bio-medical applications, e.g., bioactive coatings on bioinert metallic and ceramic substrates.
CRIS-Team Scopus Importer:2019-05-17
Keywords: Aerosol deposition; Bioactive coatings; Bioactive glasses; In vitro

Brillouin spectroscopy study of the stress-induced ferroelectric order in lead-free relaxor 0.93(Na1/2Bi1/2)TiO3-0.07BaTiO3 ceramics - Martin, Alexander; Brehl, Martin; Khansur, Neamul Hayet; Werr, Ferdinand; de Ligny, Dominique; Webber, Kyle Grant (Acta Materialia, 2022)
In this study, in situ stress-dependent Raman and Brillouin spectroscopy has been performed on polycrystalline 0.93(Na1/2Bi1/2)TiO3-0.07BaTiO3 (NBT-7BT). Brillouin scattering revealed stress-dependent changes in the elastic properties around the onset stress as well as the appearance of a transversal acoustic wave mode at elevated stress levels, which is understood to be due to the formation of long-range order. These data were compared with additional Raman scattering measurements, ex situ x-ray diffraction, and macroscopic stress-strain behavior, which revealed analogous changes in the apparent crystallographic structure and ferroelectric order in the vicinity of the onset and coercive stresses.<br

Brillouin spectroscopy study of the stress-induced ferroelectric order in lead-free relaxor 0.93(Na1/2Bi1/2)TiO3-0.07BaTiO3 ceramics - Martin, Alexander; Brehl, Martin; Khansur, Neamul Hayet; Werr, Ferdinand; de Ligny, Dominique; Webber, Kyle Grant (Acta Materialia, 2022)
In this study, in situ stress-dependent Raman and Brillouin spectroscopy has been performed on polycrystalline 0.93(Na1/2Bi1/2)TiO3-0.07BaTiO3 (NBT-7BT). Brillouin scattering revealed stress-dependent changes in the elastic properties around the onset stress as well as the appearance of a transversal acoustic wave mode at elevated stress levels, which is understood to be due to the formation of long-range order. These data were compared with additional Raman scattering measurements, ex situ x-ray diffraction, and macroscopic stress-strain behavior, which revealed analogous changes in the apparent crystallographic structure and ferroelectric order in the vicinity of the onset and coercive stresses.
CRIS-Team Scopus Importer:2022-09-09

Cooling rate calibration and mapping of ultra-short pulsed laser modifications in fused silica by Raman and Brillouin spectroscopy - Bergler, Michael; Cvecek, Kristian; Werr, Ferdinand; Brehl, Martin; de Ligny, Dominique; Schmidt, Michael (International Journal of Extreme Manufacturing, 2020)
This paper focuses on the preparation of a new extended set of calibrations of cooling rate (fictive temperature) in fused silica determined by inelastic light scattering and its subsequent use to characterize the local cooling rate distribution in ultra-short pulsed (USP) laser modifications. In order to determine the thermal history (e.g. cooling rate and fictive temperature) of fused silica, high-resolution inelastic light-scattering experiments (Raman and Brillouin spectroscopy) were investigated. Calibrations were performed and compared to the existing literature to quantify structural changes due to a change of fictive temperature. Compared to existing calibrations, this paper provides and extension to lower and higher cooling rates. Using this new set of calibrations, we characterized a USP laser modification in fused silica and calculated the local fictive temperature distribution. An equation relating the fictive temperature (Tf) to cooling rates is given. A maximum cooling rate of 3000 K min-1 in the glass transition region around 1200 °C was deduced from the Raman analysis. The Brillouin observations are sensitive to both the thermal history and the residual stress. By comparing the Raman and Brillouin observations, we extracted the local residual stress distribution with high spatial resolution. For the first time, combined Raman and Brillouin inelastic light scattering experiments show the local distribution of cooling rates and residual stresses (detailed behavior of the glass structure) in the interior and the surrounding of an USP laser modified zone.
Keywords: glass structure; ultra-short pulsed laser; fused silica; cooling rate; fictive temperature; Raman spectroscopy; Brillouin spectroscopy

Effects of Medium pH and Preconditioning Treatment on Protein Adsorption on 45S5 Bioactive Glass Surfaces - Höhn, Sarah; Zheng, Kai; Romeis, Stefan; Brehl, Martin; Peukert, Wolfgang; de Ligny, Dominique; Virtanen, Sannakaisa; Boccaccini, Aldo R. (Advanced Materials Interfaces, 2020)
Protein adsorption on 45S5 bioactive glass (BG, Bioglass) surfaces influences the biocompatibility of Bioglass and the cellular response to the material. The medium pH greatly affects protein adsorption behavior. However, the influence of pH variation on protein adsorption on Bioglass has not been investigated in detail before, although an acidifying pH has been observed in fractured or injured bone tissues. This study investigates how the medium pH (pH 7, 5, and 2) affects protein (serum albumin) adsorption on Bioglass with or without preconditioning in simulated body fluid (SBF). The results show that Bioglass can adsorb a larger amount of bovine serum albumin (BSA) than bioinert glasses at all tested pHs. The BSA adsorption on Bioglass surfaces is pH-dependent and a larger amount of adsorbed BSA is observed at lower pH (5 and 2). After preconditioning, BSA adsorption is significantly enhanced. However, the trend of pH-dependent adsorption is attenuated. No significant difference in BSA adsorption is observed at different pHs after preconditioning. The results reveal for the first time the influence of medium pH on protein adsorption on Bioglass with or without preconditioning treatment in SBF, which provides useful information for developing Bioglass based biomedical devices that will be in contact with protein-containing physiological fluids during applications.
CRIS-Team Scopus Importer:2020-05-29
Keywords: 45S5 Bioglass; bovine serum albumin; pH influence; preconditioning; surface reactivity

Enhanced Electromechanical Response and Thermal Stability of 0.93(Na1/2Bi1/2)TiO3-0.07BaTiO3 Through Aerosol Deposition of Base Metal Electrodes - Khansur, Neamul Hayet; Eckstein, Udo; Ursic, Hana; Sadl, Matej; Brehl, Martin; Martin, Alexander; Rieß, Kevin; de Ligny, Dominique; Webber, Kyle Grant (Advanced Materials Interfaces, 2021)
Na1/2Bi1/2TiO3-based relaxor ferroelectrics are extensively investigated for use in transduction applications because of their relatively large electromechanical properties. Integration of these materials into devices, however, requires better temperature stability in addition to electromechanical properties. This work demonstrates a novel approach to enhance the temperature stability of the long-range ferroelectric order as well as to enhance electromechanical properties in a non-ergodic relaxor 0.93(Na1/2Bi1/2)TiO3-0.07BaTiO3 (NBT-7BT) without changing the chemical composition through, for example, chemical substitutions or second phase particles. The approach involves the room temperature deposition of copper electrodes directly on the relaxor ceramic substrate using the aerosol deposition (AD) method. The collision of solid-state particles with the substrate surface during AD results in large impact and residual stresses, inherent to the AD process, which are shown with piezo-response force microscopy to induce long-range ferroelectric domain ordering in non-ergodic relaxor NBT-7BT. Using Raman spectroscopy, the magnitude and depth profile of the stress-induced transformation are determined. It is demonstrated that deposition-induced stresses significantly increase the temperature stability of the electromechanical properties, where long-range ferroelectric ordering is observed up to 150 °C, which is approximately 41 °C higher than NBT-7BT samples without the AD processed electrode. Moreover, the AD treatment also facilitates ferroelectric domain switching at a lower electric field, enabling maximum polarization at a relatively lower field and an enhancement in the piezoelectric response. It is shown that the deposition-induced stress is responsible for such an enhancement. Importantly, this impact-stress-driven tailoring of electromechanical properties can potentially be utilized for other functional ceramic materials as well, where internal residual stress can result in enhanced functional properties.
CRIS-Team Scopus Importer:2021-05-21
Keywords: aerosol deposition; deposition-induced stress; electromechanical applications; lead-free relaxors; temperature stability

Erratum: Cooling rate calibration and mapping of ultra-short pulsed laser modifications in fused silica by Raman and Brillouin spectroscopy (International Journal of Extreme Manufacturing DOI: 10.1088/2631-7990/ab9583) - Bergler, Michael; Cvecek, Kristian; Werr, Ferdinand; Brehl, Martin; de Ligny, Dominique; Schmidt, Michael (International Journal of Extreme Manufacturing, 2020)
In section 2.1 Correlation of fictive temperature to the cooling rate (pages 2 and 3), the equation (2) to calculate the cooling rate (qg) in the temperature domain of the glass transition was incorrectly reported. The correct equation (2) is: log (qg (Tf)) = 13 − log (η (Tf)) B = 13 − A + (Tf − T0) = 13 − (−5.66 + (Tf −19433364.15)) . (2) We stress that the results reported in the original paper, using equation (2), were calculated using the correct equation.
CRIS-Team Scopus Importer:2020-12-18

Nucleation mechanisms in a SiO2-Li2O-P2O5-ZrO2 biomedical glass-ceramic: Insights on crystallisation, residual glasses and Zr4+ structural environment - Cicconi, Maria Rita; Belli, Renan; Brehl, Martin; Lubauer, Julia; Hayakawa, T.; Kimura, K.; Hirota, T.; Usui, K.; Kohara, S.; Onodera, Y.; Lohbauer, Ulrich; Hayashi, K.; et al. (Journal of the European Ceramic Society, 2022)
In manufacturing reliable glass-ceramics, bulk chemistry and appropriate thermal treatments are critical points. To better understand the influence of nucleation parameters on the crystallisation behaviour and mechanical properties of multicomponent glass-ceramics, we studied the effects of time and temperature on phase stabilisation, the evolution of the crystal phases and physical properties of a Zr-rich lithium-silicate having a SiO2/Li2O molar ratio < 2. Here, we also provide insights into the structural environment of Zr4+ at the early stage of nucleation by Anomalous X-ray Scattering (AXS). By reverse-engineering a commercial material through remelting and sequential thermal treatments, we observed the strong effect of the nucleation temperature on the final mineral assemblage and of the volume fractions of the lithium-disilicate phase on the fracture toughness (KIc). Indeed, the KIc value was increased from ∼0.8 MPa.m½ in the pristine glass up to ∼ 2 MPa.m½, if compared to the original commercial material exhibiting a KIc value of 1.6 MPa.m½. Furthermore, the synthesis of residual glasses at different stages of the thermal treatments allowed us to observe the changes in the glass network structure and properties. AXS was used to extract the contribution exclusively coming from Zr for different nucleation steps. The differential pair distribution functions ΔZrg(r) show two distinct peaks at ∼2.10 Å and 3.44 Å, respectively associated with Zr-O and Zr-Zr/Zr-Si correlations with the formation of edge sharing in addition to corner sharing polyhedra. It was discerned the occurrence of (sub)nano-sized clusters enriched in Zr. These local clusters do not show changes during the different thermal treatments, either for higher temperatures or longer times. No Zr phases are stabilised in the crystallised materials, suggesting that these clusters do not evolve above the critical nucleus size. All evidence points to a highly heterogeneous environment and the coexistence of three structural regions i) (sub)nano Zr-clusters, ii) P enriched μ-areas, iii) residual silicate glass. The evolution and spatial distribution of these units influence the final properties.
CRIS-Team Scopus Importer:2022-01-21
Keywords: AXS; Raman; Residual glasses; Structure; Toughness; Zr

Surface Probing of Ultra-Short-Pulse Laser Filament Cut Window Glass and the Impact on the Separation Behavior - Werr, Ferdinand; Veber, Alexander; Brehl, Martin; Bergler, Michael; Werner, Dirk; Eppelt, Urs; Müllers, Ludger; de Ligny, Dominique (Advanced Engineering Materials, 2020)
The process of laser filament cutting produces a practical nongap cut which ensures high precision in lateral dimensions at the micrometer scale. Commercially available OptiWhite soda lime silicate glass is filamented using a 1064 nm picosecond pulsed Nd:YAG laser with varying burst energies and focus positions. The filaments are characterized perpendicular to the incident laser beam using scanning electron microscopy (SEM). Maximum roughness Rz evaluated with laser scanning microscopy is measured on the cut sides. The characteristic mechanical strength σ of glass cleavage is decreased by a factor of 6 with the presence of the filaments. This σ obtained in the four-point-bending setup decreases with the increase in energy deposited in the material by the laser. It is found that the cleaving cracks are guided by the filament only if the network of microcracks is sufficiently developed. A threshold of the cleaving guidance is linked to a critical surface modification width of 2.5 μm which corresponds to half the distance between filaments. The influences of the laser parameters, sample thickness, and sample position in respect of the focal plane on the cut quality are studied. Guidelines are given to define a suitable parameter set.
CRIS-Team Scopus Importer:2020-07-10
Keywords: crack guidances; filament cleaving; laser cutting; surface modifications; surface roughnesses; ultra-short-pulse laser filamentations

Thermal Evolutions to Glass-Ceramics Bearing Calcium Tungstate Crystals in Borate Glasses Doped with Photoluminescent Eu3+ Ions - Otsuka, Takahito; Brehl, Martin; Cicconi, Maria Rita; de Ligny, Dominique; Hayakawa, Tomokatsu (Materials, 2021)
Thermal evolutions of calcium-tungstate-borate glasses were investigated for the development of luminescent glass-ceramics by using Eu3+ dopant in a borate glass matrix with calcium tungstate, which was expected to have a combined character of glass and ceramics. This study revealed that single-phase precipitation of CaWO4 crystals in borate glass matrix was possible by heat-treatment at a temperature higher than glass transition temperature T-g for (100-x) (33CaO-67B(2)O(3))-xCa(3)WO(6) (x = 8-15 mol%). Additionally, the crystallization of CaWO4 was found by Raman spectroscopy due to the formation of W=O double bondings of WO4 tetrahedra in the pristine glass despite starting with the higher calcium content of Ca3WO6. Eu3+ ions were excluded from the CaWO4 crystals and positioned in the borate glass phase as a stable site for them, which provided local environments in higher symmetry around Eu3+ ions.
CRIS-Team WoS Importer:2021-03-19

Wet-chemical porosification of LTCC substrates: Dissolution mechanism and mechanical properties - Hajian, Ali; Brehl, Martin; Koch, Thomas; Zellner, Christopher; Schwarz, Sabine; Konegger, Thomas; de Ligny, Dominique; Schmid, Ulrich (Microporous and Mesoporous Materials, 2019)
Low temperature co-fired ceramics (LTCC) technology has been successfully used in microelectronics, automotive, and telecommunication applications. However, their generally high permittivity is unfavorable for micromachined devices operated at high frequencies. To overcome this drawback, we have established a wet-chemical etching process as an effective approach which can be applied to LTCC substrates in their as-fired state and allows for a local permittivity reduction in regions of interest. Understanding the etching mechanism is essential for the selection of appropriate etching conditions to control the degree of porosification. Therefore, in the present work, we report on an effective approach to achieve a tailored porosification of LTCC substrates. Different characterization techniques such as scanning and transmission electron microscopy, energy-dispersive X-ray spectroscopy, X-ray diffraction analysis, and Raman Spectroscopy were used for investigation of the morphology and chemical composition of the substrates and thereby studying the etching mechanism. Furthermore, using dynamic-mechanical analysis at temperatures up to 550 °C, the stiffness behavior of the LTCC substrates after wet-chemical etching was investigated, and promising results for the applicability of such modified modules were obtained, even when operated at elevated temperatures up to 550 °C. Finally, a practical correlation between the mechanical properties and the relative porosification depth is presented, which is independent of etching conditions and the substrate thickness, and is valuable for optimization of the suitable depth of porosification for securing the desired mechanical properties.
CRIS-Team Scopus Importer:2019-07-12